A genetic combination of silent beta-thalassaemia, high Hb A2 beta-thalassaemia, and single alpha globin gene deletion causing mild thalassaemia intermedia. Issue 2 (April 1984) - Galanello, R; Maccioni, L; Rosatelli, M C; Ibba, P; Nurchi, A M; Cao, A
Abstract : This paper reports a Sardinian patient, who was a compound heterozygote for silent beta-thalassaemia and high Hb A2 beta o-thalassaemia with the clinical phenotype of mild thalassaemia intermedia; alpha globin gene mapping showed a single alpha globin gene deletion. The reduced alpha globin chain output resulted in more balanced globin chain synthesis, which in turn accounted for the mild clinical phenotype.